Integrating private health facilities in government-led health systems: a case study of the public-private mix approach in Ethiopia - Disha Ali; Asfawesen Gebre-Yohannes Woldegiorgis; Mesfin Tilaye; Yonas Yilma; Hanna Y. Berhane; Dagmawit Tewahido; Gebeyehu Abelti; Rachel Neill; Ndeye Silla; Lauren Gilliss; Mahua Mandal (BMC, 2022)
Abstract Background Private health care facilities working in partnership with the public health sector is one option to create sustainable health systems and ensure health and well-being for all in low-income countries. As the second-most populous country in Africa with a rapidly growing economy, demand for health services in Ethiopia is increasing and one-quarter of its health facilities are privately owned. The Private Health Sector Program (PHSP), funded by the United States Agency for International Development, implemented a series of public-private partnership in health projects from 2004 to 2020 to address several public health priorities, including tuberculosis, malaria, HIV/AIDS, and family planning. We assessed PHSP's performance in leadership and governance, access to medicines, health management information systems, human resources, service provision, and finance. Methods The World Health Organization's health systems strengthening framework, which is organized around six health system building blocks, guided the assessment. We conducted 50 key informant interviews and a health facility assessment at 106 private health facilities supported by the PHSP to evaluate its performance. Results All six building blocks were addressed by the program and key informants shared that several policy and strategic changes were conducive to supporting the functioning of private health facilities. The provision of free medicines from the public pharmaceutical logistics system, relaxation of strict regulatory policies that restricted service provision through the private sector, training of private providers, and public-private mix guidelines developed for tuberculosis, malaria, and reproductive, maternal, newborn, child, and adolescent health helped increase the use of services at health facilities. Conclusions Some challenges and threats to sustainability remain, including fragile partnerships between public and private bodies, resource constraints, mistrust between the public and private sectors, limited incentives for the private sector, and oversight of the quality of services. To continue with gains in the policy environment, service accessibility, and other aspects of the health system, the government and international communities must work collaboratively to address public-private partnerships in health areas that can be strengthened. Future efforts should emphasize a mechanism to ensure that the private sector is capable, incentivized, and supervised to deliver continuous, high-quality and equitable services.